Enhancing information-based spaces using IoT and multimedia visualization - a case study - Pedro José Ayala Casanova (2018)
The main objective of this research is to make an exploration around conceptual frameworks, state of the art and plausible applications of the Internet of Multimedia Things in distributed services for creating augmented environments that contribute to enhance the collective experience and participation of people attending professional conferences, group meetings and public spaces in general. Thus, the methodology will be based on a review of the state of the art of IoT technologies applicable for multimedia things and information visualization, specially in the context of augmented public spaces, where the access of high-quality data can be possible without preventing real-world interaction among attendants, as well as improving the overall experience of participants, considering also technological solutions designed for the events of limited time-frames.